Diversity in daytime and night‐time transpiration dynamics in barley indicates adaptation to drought regimes across the Middle‐East. (7th February 2019) - Sadok, Walid; Tamang, Bishal G.
Abstract: A challenge to breeding drought‐tolerant barley in the Middle‐East is that precipitation and evaporative demand patterns dictate opposite water use strategies (conservative vs. risk‐taking). To characterize these strategies, we examined high‐resolution, whole‐plant transpiration rate (TR) responses to increasing vapour pressure deficit (VPD) and nocturnal TR (TRN ) dynamics among 25 local barley genotypes, using a novel phenotyping system. These traits were specifically selected because they exist under modalities enabling the expression of both strategies. The genotypes were selected from locations spread across a large aridity gradient represented by temperature and precipitation data spanning 30 years. Here, we uncovered a substantial diversity in TR responses to VPD where slopes of the linear responses correlated negatively with local maximal temperatures, pointing to opposite drought tolerance strategies. Low canopy conductance (low slopes) was associated with higher aridity, likely to enable water‐saving, while higher conductance was associated with wetter areas, likely to enable a more aggressive water use to maximize physiological activity. TRN was highly diverse and represented up to 15% of maximal daytime TR, pointing to the possibility of increasing water‐saving by reducing TRN . Furthermore, we detected pre‐dawn variation in TRN that negatively correlated with local precipitation, indicating that a tighter circadian control is associated with adaptation to drought, consistently with a circadian resonance mechanism. These findings indicate that canopy conductance and TRN are potentially beneficial to design drought‐tolerant barley germplasm adapted to different drought regimes taking place in the Middle‐East.